(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Sugarcane is a perennial grass that is planted in various regions of the country. Each state has a unique Sugarcane need, and each state requires a comparatively large quantity of Sugarcane for that particular industrial application. However, it is a question of study to determine which state in India requires more sugarcane for a certain industrial requirement. It will be easier to enhance crop output according to the industrial demand in that state by evaluating the relative demand of sugarcane for industrial production of certain items. Thus, the current study sheds light on the demand for sugarcane for various purposes in the states of Uttar Pradesh, Gujarat, Maharashtra, and Tamil Nadu, and it pave the way for future research into the relationship between different varieties of cereals and pulses and average consumption of that variety in a given state.